2010
DOI: 10.1051/0004-6361/200913549
|View full text |Cite
|
Sign up to set email alerts
|

A large crater as a probe of the internal structure of the E-type asteroid Steins

Abstract: Context. The detection of a large crater (2 km in diameter) on Steins, a diamond-shape asteroid with a diameter of only about 4.6 km, was a large surprise given the size of the asteroid itself. Steins belongs to the rare class of E-type asteroids, which had not been observed by any spacecraft before the Rosetta mission of the European Space Agency (ESA) in 2008. Aims. We demonstrate that this large crater places constraints on both the internal structure of Steins and its age based on crater counting. Methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…The possibility that this ratio is relatively large for a small body has prompted attempts to explain it, such as modelling of potential impacts in terms of possible macro or micro porosity of the body (e.g. Michel et al, 2009;Jutzi et al 2010 Indeed it is more akin to the cases of (433) km and based on analysis of a data set of 205,770 asteroids, compared to 12,487 in Zappalà et al, 1995). Antiope was identified as a synchronous pair by direct imaging (Merline et al, 2000) and was later subject to an extended programme of ground based observations to accurately determine its light curve (Descamps et al, 2007).…”
Section: (2867) Steinsmentioning
confidence: 99%
“…The possibility that this ratio is relatively large for a small body has prompted attempts to explain it, such as modelling of potential impacts in terms of possible macro or micro porosity of the body (e.g. Michel et al, 2009;Jutzi et al 2010 Indeed it is more akin to the cases of (433) km and based on analysis of a data set of 205,770 asteroids, compared to 12,487 in Zappalà et al, 1995). Antiope was identified as a synchronous pair by direct imaging (Merline et al, 2000) and was later subject to an extended programme of ground based observations to accurately determine its light curve (Descamps et al, 2007).…”
Section: (2867) Steinsmentioning
confidence: 99%
“…The surface is covered by several craters (Keller et al 2010;A&A 531, A168 (2011) Marchi et al 2010), with a large crater (2 km) near the south pole. A rubble pile internal structure has been proposed (Jutzi et al 2010) and the equatorial bulge may have been created by the YORP effect in the past. Statistical analysis of the surface in visible wavelengths has proved that the reflectivity is very homogeneous (Leyrat et al 2010), as also expected by Dotto et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…This model was used to study the creation of asteroid families, as well as a study on asteroid Šteins by Jutzi et al (2010a), that revealed a preference for an monolithic interior of Šteins before the impact that formed the largest crater Benavidez et al 2012 Diamond transformed it into a rubble pile body that is seen today. …”
Section: Simulating Impacts On Rubble Pile Asteroidsmentioning
confidence: 99%
“…• The impact that formed the crater Diamond at the southern pole will have shattered the body even if it was monolithic before (Jutzi et al 2010a). …”
Section: šTeins As a Rubble Pile Asteroidmentioning
confidence: 99%